2014
DOI: 10.1093/aob/mcu176
|View full text |Cite
|
Sign up to set email alerts
|

Female and male fitness consequences of clonal growth in a dwarf bamboo population with a high degree of clonal intermingling

Abstract: The results, in conjunction with previous studies, emphasize the role of the spatial arrangement of genets on both the quantity and quality of offpsring, and suggest that an intermingled distribution of genets can reduce the mating costs of clonal growth and enhance overall fitness, particularly female fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
0
24
0
2
Order By: Relevance
“…They concluded that pollen dispersal distances were sufficiently high to mitigate local mate scarcity despite extensive clonal growth. By contrast, however, clonal intermingling has been shown to be associated with reduced mating costs of clonal expansion in other plants (7,38). Therefore, whether the two exceptions mentioned above really are exceptions to the pattern we predict here or more generally reflect mating patterns in clonal plants will be revealed as more studies of the mating patterns of clonal plants are conducted.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…They concluded that pollen dispersal distances were sufficiently high to mitigate local mate scarcity despite extensive clonal growth. By contrast, however, clonal intermingling has been shown to be associated with reduced mating costs of clonal expansion in other plants (7,38). Therefore, whether the two exceptions mentioned above really are exceptions to the pattern we predict here or more generally reflect mating patterns in clonal plants will be revealed as more studies of the mating patterns of clonal plants are conducted.…”
Section: Discussionmentioning
confidence: 50%
“…However, a study of a highly intermingled stand of the bamboo Sasa veitchii var. hirsuta showed that selfing rates were independent of genet size (38). On one hand, this might reflect broad pollen dispersal in S. veitchii; under broad dispersal, we expect only a weak association between clone size and selfing rates (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Sexdependent pattern in clonal plants has been revealed also for mortality (Allen and Antos 1993) and reproductive success (Matsuo et al 2014). No doubt all of these life-history traits may have an impact on population dynamics and demography which are closely related with fine-scale SGS.…”
Section: Communicated By P Ingvarssonmentioning
confidence: 96%
“…Similarly to other monocarpic, monopodial genera of Bambuseae Shibata, 2012, 2014;Matsuo et al, 2014) Phyllostachys are monocarpic, and reproduce mainly vegetatively (Isagi et al, 2016) from nodal shoots developing from the underground rhizome system (Ito et al, 2015) which comprises 39-57 % of the total biomass (Umemura and Takenaka, 2014). Phyllostachys edulis (syn.…”
Section: Review Of Literaturementioning
confidence: 99%